Growth of generative explants of Moringa oleifera on different culture conditions - Muslihatin, Wirdhatul; Rizkia, Hanum Laila (Proceeding International Conference on Global Resource Conservation, 2015)
In vitro culture is more effective propagation technique because the propagation time is faster than conventional propagation so the achievement of the results is in favor of the improvement program and faster spread of Moringa oleifera. The objectives of this study were to determine the effect of carbon source and photoperiod on the growth of generative explants of M. oleifera in vitro. The method performed were inoculation of generative explans on MS Medium, observation growth of callus, and measurement of fresht weigth of callus. The generative explants used were M. oleifera seeds grown on MS medium with 3%, 5%, 7% and 9% sucrose and then they were cultured with photoperiod of 12/12, 14/10, and 16/8 hours (light/dark). The results showed that the best response of growth callus was indicated by the explants cultured on 3% sucrose medium in the photoperiod of 12/12.Keywords: Moringa oleifera; nodule; photoperiod; sucrose